Anemia and Wasting in Adolescent Girls: A Cross-Sectional Study in Aceh, Indonesia - Ahmad, Aripin; Azizah, Amelia Puteri Nur; Arnisam, Arnisam; Phebe, Natasya; Arifin, Syuja Rafiqi (Jurnal Gizi dan Pangan, 2023)
The purpose of this study was to assess the anemia and nutritional status in adolescent girls. A cross-sectional study was conducted on 348 senior high school girls. Nutritional status was determined by BMI-for-age Z-score for those younger than 19 years and BMI for those older than 19 years. Anemia was determined using the standard of severely low hemoglobin level of less than 12 mg/dL. Data analysis used the logistic regression test at the 95% confidence interval. The results showed that 40.5% of adolescent girls had anemia, 50.9% were wasted, and 14.4% were overweight/obese. Wasting and obesity are risk factors for anemia in adolescent girls. Intervention is needed to prevent anemia and wasting by improving balanced diet and nutrition education.